2011
DOI: 10.1378/chest.10-2472
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Natriuretic Peptide Concentrations to Central Sleep Apnea in Patients With Heart Failure

Abstract: Background: Central sleep apnea (CSA) is frequent among patients with heart failure (HF) and associated with increased morbidity and mortality. Elevated cardiac fi lling pressures promote CSA and atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) secretion. We hypothesized that circulating natriuretic peptide concentrations predict CSA. Methods: Consecutive patients with HF (n 5 44) with left ventricular ejection fraction (LVEF) Յ 35% underwent polysomnography for detection of CSA. CSA was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 50 publications
4
21
1
1
Order By: Relevance
“…In these patients, higher eAHI values indicated a much worse hemodynamic function (lower LVEF and higher NT-proBNP values) and a higher rate of supraventricular arrhythmia. Relations between natriuretic peptide levels, LVEF and SDB in heart failure were documented in the literature [20,21]. Our findings are also consistent with previous reports of SDB promoting supraventricular arrhythmia, including both premature supraventricular beats and atrial fibrillation [22].…”
Section: Discussionsupporting
confidence: 92%
“…In these patients, higher eAHI values indicated a much worse hemodynamic function (lower LVEF and higher NT-proBNP values) and a higher rate of supraventricular arrhythmia. Relations between natriuretic peptide levels, LVEF and SDB in heart failure were documented in the literature [20,21]. Our findings are also consistent with previous reports of SDB promoting supraventricular arrhythmia, including both premature supraventricular beats and atrial fibrillation [22].…”
Section: Discussionsupporting
confidence: 92%
“…The signifi cantly elevated NPs in our subject cohort are also aligned with previous investigations that found ANP and BNP concentrations to be elevated in patients with HF and CSA. 9,10 Subjects with CSA had more severe HF, including evidence of hyperventilation at rest and during exercise, compared with patients with HF without CSA, in agreement with prior report. 34 In addition to the relationship between low leptin and CSA, our data showed that leptin concentration was signifi cantly and inversely correlated with e / co 2 at rest and during exercise and with e and V t during exercise, and was positively correlated with rest and exercise P etco 2 .…”
Section: Discussionsupporting
confidence: 89%
“…7,8 Natriuretic peptides (NPs) are also increased in proportion to the hemo dynamic severity of HF, and elevated circulating con centrations have been associated with the presence of CSA. 9,10 Leptin is an adipokine that regulates food intake and energy expenditure. 11 Since its discovery, leptin has emerged as a pleiotropic hormone studied extensively in the setting of cardiovascular diseases [12][13][14][15][16] and also appears to be important in the regulation of ventilatory control.…”
Section: Original Research Sleep Disordersmentioning
confidence: 99%
“…Although central sleep apnea is less amenable to treatment with CPAP, clinicians must be aware of its prognostic and therapeutic implications in patients with heart failure. [35,36]…”
Section: Discussionmentioning
confidence: 99%